Receptors and Hormone Action / Volume I - Birnbaumer Lutz; O'Malley Bert W (Allyn And Bacon, 1977)
Preface, Sequence Organization of Eukaryotic DNA, The Eukaryotic Nucleus, Chromatin Structure, Functional Organization of Chromatin, Animal Nuclear RNA Polymerases, Synthesis and Processing of Eukaryotic Messengeer RNA, Purification and Characterization of Eukaryotic RNA and Unique Sequence Genes, Analysis of Cellulae Messenger RNA Using Complementary DNA Probes, Gene Expression in the Eukaryotic Cell, Regulation of Gene Expression in the Eukaryotic Cell, Steroid Hormone Receptors: Basic Principles and Measurement, Current Views on the Organization of Lipids and Proteins in Plasma Membranes, Fluidity in Membranes, Reconstitution of the Coupled Transports of Na+ k +ATPase, Solubilization and Characterization of Adenylyl Cyclase: Approaches and Problems, The Actions of Hormones and Nucleotides on Membrane Bound Adenylyl Cyclases: An Overview, An Approach to the Study of the Kinetics of Adenylyl Cyclase, Index.